PREVENTIVE STRATEGIES OF THE CENTRAL KALIMANTAN REGIONAL POLICE AGAINST NARCOTICS DISTRIBUTION AMONG UNIVERSITY STUDENTS IN ACCORDANCE WITH LAW NO. 35 OF 2009 ON NARCOTICS - Jenika; Aristoteles; Andika Wijaya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The abuse and distribution of narcotics among university students remains a growing concern, particularly in Central Kalimantan. This study aims to analyze the Upayaes and approaches implemented by the Central Kalimantan Regional Police (POLDA Kalteng) in preventing drug circulation within academic environments, especially in reference to the enforcement of Law No. 35 of 2009 on Narcotics. Utilizing a juridical-empirical method, data were collected through interviews, field observations, and literature studies. The findings reveal that the police have initiated several preventive measures including public campaigns, educational outreach, utilization of social media platforms, and formal collaborations with universities through the formation of Anti-Narcotics Task Forces. However, these initiatives, especially those focused directly on students, remain inconsistent and often event-based. Legal enforcement has been applied equally, with no exemption for students, while still allowing for rehabilitation alternatives for non-distributing users. The main challenges faced include limited funding, low student participation, weak family reporting, and inadequate intersectoral coordination. This study recommends enhancing structured and continuous drug prevention programs on campus, strengthening institutional support from universities and student organizations, and increasing family involvement in early detection and intervention. The outcomes of this research are expected to support the development of more effective anti-narcotics policies within higher education institutions and to promote a more vigilant and resilient campus culture against drug abuse.